A Case of Anterior Spinal Artery Syndrome Caused by Streptococcus mitis Endocarditis - Aria Mahtabfar; Hamoon Eshraghi; Melroy D’Souza; William Berrigan; Kathleen Casey (Case Reports in Medicine)
Background. Infectious endocarditis (IE) typically occurs in the setting of intravenous drug use, prosthetic heart valves, or rheumatic heart disease. However, there are a few reports of IE occurring in the setting of immunosuppression secondary to cancer and/or chemotherapy. Here, we present a case of a cancer patient who developed anterior spinal artery (ASA) syndrome secondary to a septic embolus from IE. Case Presentation. A 78-year-old male with a history of gastroesophageal cancer treated with chemotherapy and radiation presented to the hospital after a fall at home. He reported experiencing dyspnea and orthopnea for two weeks prior to presentation. In the ED, his vital signs were stable, and his examination was significant for a flaccid paralysis of the right lower extremity. Diagnosis of septic emboli secondary to IE was made after the echocardiogram showed the presence of vegetations on the aortic valve, blood cultures were positive for Streptococcus mitis, and thoracic spine MRI was indicative of an infarction at T10. Discussion. This case highlights the presence of IE in the setting of cancer and chemotherapy. Although cancer is a rare cause of IE, clinicians must maintain a high index of suspicion in order to minimize the sequelae of IE.